2006
DOI: 10.2220/biomedres.27.183
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of muscle fatigue by catchlike-inducing intermittent electrical stimulation in rat skeletal muscle

Abstract: Catchlike property is the force enhancement produced when a brief, high-frequency burst of pulses is added to a constant low-frequency stimulation. In functional electrical stimulation, constant low-frequency stimulation of approximately 20 Hz has primarily been used to reduce muscle fatigue. The purpose of this study was to investigate the effects of catchlike-inducing intermittent stimulation on muscle fatigue in relation to continuous intermittent low-frequency stimulation. Twenty-two adult male Wistar ST r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Some research has addressed the attenuation or delay of FES-induced fatigue. Optimal stimulation patterns, such as Nlets [6] or catch-like stimulation [7], were found to maximize muscle performance and minimize fatigue. Random modulation of FES parameters was proved to have no effect on muscle fatigue [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some research has addressed the attenuation or delay of FES-induced fatigue. Optimal stimulation patterns, such as Nlets [6] or catch-like stimulation [7], were found to maximize muscle performance and minimize fatigue. Random modulation of FES parameters was proved to have no effect on muscle fatigue [8].…”
Section: Introductionmentioning
confidence: 99%
“…General anesthesia was induced by intraperitoneal injection of sodium pentobarbital (30 mg/kg body weight). After opening the posterior surface of the right leg to expose the sciatic nerve in the gluteal region, a bipolar cuff electrode (inter-electrode distance, 5 mm; MD Giken, Tokyo, Japan) was attached to the sciatic nerve (37) (Fig. 1).…”
mentioning
confidence: 99%
“…A transducer (Orientec, Tokyo, Japan) was attached and fixed next to the stump with a load of 1 N (37). Signals transmitted from the force transducer during isometric muscular contraction were recorded on a force-time curve using a paper recorder (Nihon Kohden, Tokyo, Japan) (37). To prevent muscle desiccation during the study, the exposed area was covered with mineral oil.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There were several reports on the study of intermittent electrical stimulation. [34][35][36] Matsunaga et al 35 and Shimada et al 36 showed that high-frequency electrical stimulation elicits less fatigue than low-frequency electrical stimulation during a repetitive stimulation protocol. Dreibati et al 34 reported that only high-frequency (100 Hz) intermittent electrical stimulation within 5 minutes met the criteria of appropriate muscle force training.…”
Section: Discussionmentioning
confidence: 99%